Imaging post liver transplantation part II: biliary complications. Issue 11 (November 2020) - Allard, R.; Smith, C.; Zhong, J.; Sheridan, M.; Guthrie, A.; Albazaz, R.
Abstract : Biliary complications post liver transplantation are a significant source of morbidity and mortality and early recognition is paramount to the long-term success of the liver graft. Part II of this series will focus on liver transplant biliary anatomy, including the blood supply to the biliary system and potential problems if it is interrupted. The imaging rationale for investigating suspected biliary complications, potential pitfalls, and treatment options will be discussed. The various biliary complications will be illustrated using a collection of cases.